MODEL EDUKASI BERBASIS PELATIHAN KADER UNTUK MENINGKATKAN KAPASITAS DETEKSI DINI STUNTING - Ritiauw, Benico; Surya, Adnan Triputra; Dwiardhana, Arya Raditya; Ubro, Maurin Valeria (PAKEM: Jurnal Pengabdian Kepada Masyarakat, 2026)
Stunting is a condition of short stature in children based on length or height-for-age that is below -2 standard deviations, which can be observed through delayed growth and development as well as nutritional status. Stunting can be caused by various factors, including family conditions, environmental factors, and the availability of health services. The prevalence of stunting in Central Maluku Regency in 2025 is reported at 27%, with six subdistricts identified as locus areas, namely Seram Utara, Nusa Laut, Salahutu, Amahai, Pulau Haruku, and Leihitu. The purpose of this community service activity carried out by university students participating in the Community Service Program (KKN) in collaboration with Masohi City Health Center is to provide interventions for Posyandu cadres as promoters for the prevention and early detection of stunting in Ampera Village, Masohi City District, which is one of the covered areas of Central Maluku Regency. The implementation stages were arranged systematically, consisting of planning, location survey, and program execution. The outcome of this community service activity was the formation of Posyandu cadres who are educated about stunting and skilled in conducting examinations for infants and toddlers